Morpho-Anatomical and Molecular Characterization of the Oversprouting Symptoms Caused by Fusarium decemcellulare in Guarana Plants (Paullinia cupana var. sorbilis) - Queiroz, Cláudia Afras de; Silva Matos, Kedma da; Lobo, Igor Kelvyn Cavalcante; Sousa, Sandra Barbosa de; Muniz, Celli Rodrigues; Beleza Yamagishi, Michel E.; Zocolo, Guilherme Julião; Hanada, Rogério Eiji; Gasparotto, Luadir; Sousa, Nelcimar Reis; Andrade, E. V. de; Cordeiro, Isabelle Bezerra; et al. (Tropical Plant Biology, 2020)
Oversprouting is a poorly studied disease of guarana plant (Paullinia cupana var. sorbilis), a native species from Amazon Rainforest caused by Fusarium decemcellulare (FDC) that affects the plant growth and reproduction, severely compromising productivity. The sorbilis variety of guarana is anciently cultivated and is used today for the industry of soft drinks, cosmetic and pharmaceutical. Transcriptome, proteome, light and electron microscopy were used to compare symptomatic and asymptomatic tissues and reveal anatomical, histological and cytological alterations resultant from the disease. Disease symptoms described here include a marked reduction in the longitudinal axis and the formation of “capsules”, named as this for the first time here, which display hard thickened external walls and contain extremely malformed floral organs and/or poorly differentiated vegetative primordia when occurring isolate in individual branching points. The aggregate of multiple “capsules” in a same branch point produces galls. The production of indol-acetic acid (IAA) in vitro by F. decemcellulare was for the first time reported and the comparative transcriptome and preliminary proteome data from symptomatic and asymptomatic tissues, support the occurrence of hormonal imbalance identified through several plant hormone-related genes and proteins differentially expressed only in symptomatic tissues. Auxin signaling mechanism, as well as auxin-responsive genes associated to cell cycling, division and proliferation also occurred differentially in infected tissues. Oversprouting and the reduction of the longitudinal axis in malformed cells and organs are related to hormonal unbalance are discussed in this paper. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Auxin; Galls; Guarana plant; Plant-pathogen interaction; Proteomic; Transcriptomic; en